2019
DOI: 10.1371/journal.pone.0216252
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of HIV detection among breastfeeding postpartum Kenyan women eligible under Option B+

Abstract: Background The Option B+ strategy streamlines delivery of HIV antiretroviral therapy (ART) to pregnant women, but concerns remain about ART treatment adherence and long term outcomes. Methods We conducted a retrospective analysis of a cohort of HIV-positive, postpartum breastfeeding women receiving ART via Option B+ in Nairobi, Kenya. The primary outcome was virologic failure in plasma (HIV RNA >1000 copies/mL), and detection in breast milk (>150 copies/mL) and endocerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Our findings are consistent with other studies from SSA, which report 6-20% prevalence of virologic non-suppression among women on Option B+ [6,[27][28][29][30]. However, most of these studies evaluated VL postpartum following ART initiation in pregnancy, in contrast to our study which focused on pregnancy.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are consistent with other studies from SSA, which report 6-20% prevalence of virologic non-suppression among women on Option B+ [6,[27][28][29][30]. However, most of these studies evaluated VL postpartum following ART initiation in pregnancy, in contrast to our study which focused on pregnancy.…”
Section: Discussionsupporting
confidence: 91%
“…Accumulating evidence has shown that giving antiretroviral medicines to the mother or the infant significantly reduces the risk of HIV transmission through breastfeeding (98). A study by Chan et al (99) on HIV detection among 42 breastfeeding Kenyan women showed that at 6-14 wk postpartum, 21.4% had HIV RNA detected in plasma and 14.3% in breast milk. However, when adjusting the time of beginning ART, earlier ART initiation in pregnancy was significantly associated with plasma suppression of the virus.…”
Section: Prevention Of Mtct Of Hivmentioning
confidence: 99%